Предмет: Математика,
автор: NekLegoBoy
найдите значение выражения. 8-6x-(-5x+(-4x)) при x=2
Ответы
Автор ответа:
0
8 - 6х + 5х + 4х = 8 + 3х
8 + 3×2 = 8 + 6 = 14
8 + 3×2 = 8 + 6 = 14
Автор ответа:
0
8-6x-(-5x+(-4x)) при x=2
8-6x-(-5x+(-4x)) =8-6х-(-5х-4х)=8-6х+5х+4х=8+3х=8+3*2=8+6=14
8-6x-(-5x+(-4x)) =8-6х-(-5х-4х)=8-6х+5х+4х=8+3х=8+3*2=8+6=14
Похожие вопросы
Предмет: История,
автор: upastuh46
Предмет: Математика,
автор: damirgggg7777
Предмет: Математика,
автор: aidamelek79
Предмет: География,
автор: vlubkov
Предмет: Математика,
автор: Romanova73